What women should know about emergency contraception - analysis of women’s awareness and experiences after its use - Śnieżek, Kinga; Dobko, Katarzyna; Frącz, Gabriela; Glac, Agata; Kuliga, Klaudia; Musz, Kinga; Sejnowska, Natalia; Socha, Agnieszka; Surowiec, Agata; Zając, Anna (Journal of Education, Health and Sport, 2023)
Introduction: Emergency contraception is a method of contraception instigated when the other ones have failed or after unprotected sex. Although highly effective, it is subject to the risk of side effects. Aim of the study: The purpose was to assess the women’s knowledge regarding emergency contraception methods and to analyze the experience related to the use of levonorgestrel and ulipristal acetate. Materials and methods: The research was done by conducting an anonymous online survey. The study took place in May 2023 and included 214 women over 15 years of age. The results were analyzed in Excel with a consideration of scientific literature. Results: 64.5% of women indicated correctly what emergency contraception is, 13.1% misunderstood its definition. 86% of respondents were unaware that the emergency contraception could be used for up to 120 hours after sex. 45% of women who used emergency contraception had difficulties obtaining a prescription. 35% of those surveyed indicated that they had side effects, the two most commonly reported being nausea and fatigue. Conclusions: Most women know the definition of emergency contraception, however, the vast majority of the respondents failed to specify how soon the emergency contraception shall be implemented after the intercourse. A large percentage of women reported difficulties in obtaining a prescription for emergency hormonal contraceptives. Therefore, the society should be better educated when it comes to emergency contraception and further actions should be implemented to improve its availability.